In Vitro Susceptibility of Methicillin-Resistant Staphylococcus aureus and Methicillin-Susceptible Staphylococcus aureus to a New Antimicrobial, Copper Silicate - Carson, Kerry C. (American Society for Microbiology (ASM), 2007)
The soluble copper silicate (CS) MIC of 100 strains of methicillin-resistant Staphylococcus aureus and 100 strains of methicillin-susceptible S. aureus (MSSA) was 175 mg Cu/liter. Bactericidal and postantibiotic effects (≥1 h) were seen at 2× MIC and 4× MIC. The frequency of mutation was <10(−9), and serial passage could not extend growth beyond 1.6× MIC.